Modernizing a Classic Test: Validation and Clinical Utility of Infrared-Barrier and Near-Infrared Photometry for Erythrocyte Sedimentation Rate Determination - Ester Maduma Napitupulu; Malayana Rahmita Nasution; Ricke Loesnihari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The erythrocyte sedimentation rate (ESR) is a cornerstone laboratory test for monitoring inflammation. The manual Westergren method, while the established gold standard, is slow and hazardous, prompting a shift towards automation. This study provides a rigorous, head-to-head validation of two mechanistically distinct automated technologies—infrared-barrier photometry (IBP) and near-infrared photometry (NIP)—to assess their analytical performance and operational utility in a tertiary care setting. Methods: A cross-sectional method comparison study was conducted on 59 outpatient samples at Adam Malik General Hospital, Indonesia. Each sample was analyzed for ESR using the manual Westergren method, the Caretium XC-A30 analyzer (IBP), and the Mindray BC-760 hematology analyzer (NIP). Method agreement was assessed using Passing-Bablok regression and Bland-Altman analysis. Clinical concordance was evaluated using categorized results. Results: Both automated methods demonstrated excellent agreement with the Westergren reference. Passing-Bablok regression showed no significant proportional or constant bias for either method. The NIP method exhibited a near-perfect regression equation (y = 1.01x - 0.58), while the IBP method also performed well (y = 0.98x + 1.25). Bland-Altman analysis revealed a clinically insignificant mean bias of +0.44 mm/hr for NIP and -4.47 mm/hr for IBP. Clinical concordance was high, with 96.6% of NIP results and 91.5% of IBP results falling within the same clinical category as the Westergren method. Conclusion: Both automated methods are valid and reliable alternatives to the Westergren method. The NIP technology, in particular, offers a substantial leap in laboratory efficiency by providing results in under two minutes from a standard EDTA sample. Its superior workflow integration and strong analytical performance support its adoption to drastically reduce turnaround times and enhance modern patient care pathways.